PROSEDUR PEMERIKSAAN RADIOGRAFI SINUS PARANASAL (SPN) DENGAN KASUS SINUSITIS - Nada Nabilah; Agustina Dwi Prastanti; Darmini Darmini3 (JRI (Jurnal Radiografer Indonesia), 2023)
ABSTRACT Background : The radiographic procedure of the paranasal sinuses according to Long et al., (2016) uses Lateral projection, Caldwell Method, Parietoacanthial (Open Mouth and Closed Mouth) and Submentovertical. Caldwell method projection can be done with the image receptor 150 angled technique and the vertical image receptor technique by attaching the image receptor and propping the forehead with a soft bag. However, the radiographic examination procedure of the paranasal sinuses at the Radiology Installation of RSUD Karanganyar was carried out on the caldwell method projection, using a vertical image receptor technique, the patient's forehead and nose attach to the image receptor without a soft bag. Methods :The purpose of this study was to determine the radiographic examination procedure of the paranasal sinuses in cases of sinusitis and to find out the reasons for using the Caldwell Method with the patient's forehead and nose attached to the image receptor without a soft bag. This type of research is a qualitative with a case study approach This research was conducted by means of observation, documentation, and deepening with radiology specialists and radiographers. Observational data were processed and analyzed using open coding, interview data were processed, analyzed, and presented in the form of quotations so that conclusions could be drawn. Results : The results showed that the radiographic examination of the paranasal sinuses at the Radiology Installation of RSUD Karanganyar used a Lateral projection, Waters Closed Mouth, and Caldwell Method with a vertical image receptor technique and adjustment of the position of the forehead and nose against the image receptor. Conclusion : The reason the forehead and nose are positioned against the image receptors in the Caldwell Method projection is for convenience and to view the frontal sinus clearly without magnification.